Cowboy Pug : The Adventures of Pug Series #2 - James, Laura, 1979-; Ceulemans, Eglantine (New York : Bloomsbury, 2017)
Pug and his faithful companion, Lady Miranda, are pretending to be cowboys for the day, and soon get into mischief.
Keywords: Pug -- Fiction; Dogs -- Fiction; Play -- Fiction; Friendship -- Fiction